The Role of the Circular Economy in Economic Development: An Empirical Investigation for Panel of Some Selected European Economies - Abdelkarim Jabri; Rachid Yahyaoui (Comparative Economic Research)
This study examines the relationship between the circular economy and economic development in 14 EU countries for the period 2000–2020. Compared to previous work, we emphasize the importance of taking into account cross‑dependencies and heterogeneity between the countries making up the Panel. Furthermore, the cointegration relationship employed in this work considers structural shocks and cross‑dependencies using the test of Westerlund and Edgerton. This last test made it possible to validate the long‑term relationship in the model. This study used the augmentedmean group technique to overcome some economic problems. Using Kónya’s bootstrap panel causality test, we found that the causal relationship is only found in a few countries. According to the empirical analysis conducted in this work, our findings indicate that economic growth, research and development and the generation of municipal waste favor the recycling and composting of municipal waste. In the same way, the recycling of municipal waste, research and development expenditure and the Generation of municipal waste increase positively the economic growth rate. Our empirical results provide important policy implications for 14 EU countries that need to take adequate measures to improve the recycling rate through environmentally friendly technology to achieve a level of sustainable growth and development. Compared to previous studies, this work attempts to fill a gap in current research and enrich the existing literature between the circular economy and economic development in Europe.